2021
DOI: 10.5206/ijoh.2022.1.13607
|View full text |Cite
|
Sign up to set email alerts
|

The Best Thresholds for Rapid Identification of Episodic and Chronic Homeless Shelter Use

Abstract: This paper explores how to best identify clients for housing services based on their homeless shelter access patterns. We utilize the number of shelter stays and episodes of shelter use for a client within a specified time window. Thresholds are then applied to these values to determine if that individual is a good candidate for housing support. Using new housing referral impact metrics, we explore a range of threshold and time window values to determine which combination both maximizes impact and identifies g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…This shortcoming can be addressed by applying the techniques in this paper to a data set that has been augmented to include individuals sleeping outside, possibly using input from street outreach teams. Cluster analysis has previously demonstrated that the client shelter access patterns in the DI data set are broadly representative of most North American emergency shelters [25]. While the rules presented in this paper should be a reasonable starting place for most shelters, it is still best for each shelter seeking to apply our techniques to first conduct a new rule search on their own client data.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This shortcoming can be addressed by applying the techniques in this paper to a data set that has been augmented to include individuals sleeping outside, possibly using input from street outreach teams. Cluster analysis has previously demonstrated that the client shelter access patterns in the DI data set are broadly representative of most North American emergency shelters [25]. While the rules presented in this paper should be a reasonable starting place for most shelters, it is still best for each shelter seeking to apply our techniques to first conduct a new rule search on their own client data.…”
Section: Discussionmentioning
confidence: 98%
“…This makes them much easier to implement using a database interface that supports basic thresholding and logical operators. While work has previously been done exploring threshold testing for chronic shelter use identification [25,26], this work lacks the rigor of a formalized rule search framework that optimizes rule selection based on a performance metric.…”
Section: Introductionmentioning
confidence: 99%